PEMETAAN VARIASI RENDANG DI SUMATERA BARAT - Gusriani i; Rery Novio (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
This research was conducted in West Sumatra considering that West Sumatra has a unique culinary worldwide. Therefore, the research objectives of this study were 1) to find out the rendang variants in West Sumatra, 2) to find out the distribution of rendang variants in West Sumatra through mapping. by utilizing the Geographic Information System (GIS). Interactive model analysis techniques through components of data collection, data reduction, and data presentation and drawing conclusions or verification. using primary data through interviews with Minang women in regencies and cities in West Sumatra. The conclusion of this study is that there are fourteen variations of rendang spread across West Sumatra, namely beef rendang, chicken rendang, egg rendang, Wednesday or lung rendang, rendang spikes, bada maco rendang, cubadak rendang (jackfruit), yam shoots rendang (cassava leaves), pensi rendang, lokan rendang, bungo jua rendang (johar flower), eel rendang, fish rendang, pork rendang.